Future Challenges in Crop Protection Against Fungal Pathogens - Goyal, Aakash; Manoharachary, Chakravarthula; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This volume presents the issues and challenges of crop pathogens and plant protection. Composed of the latest knowledge in plant pathology, the book covers topics such as fungal diseases of the groundnut, plant growth promoting rhizobacteria, plant pathogenic fungi in the genomics era, the increased virulence of wheat rusts, and oat fungal diseases. Written by experienced and internationally recognized scientists in the field, Future Challenges in Crop Protection Against Fungal Pathogens is a concise yet comprehensive resource valuable for both novice as well as experienced plant scientists and researchers.
Fungal Diseases of Groundnut: Control and Future Challenges -- Plant Growth Promoting Rhizobacteria in Crop Protection and Challenges -- Understanding the Mechanism Involved in PGPR Mediated Growth Promotion and Suppression of Biotic and Abiotic Stress in Plants -- Downy Mildew Disease of Pearl Millet and Its Control -- Research on Plant Pathogenic Fungi in the Genomics Era: From Sequence Analysis to Systems Biology -- Pre and Post Harvest Diseases of Potato and Their Management -- Host-Pathogen Interaction, Plant Diseases, Disease Management Strategies and Future Challenges -- Ug99-Future Challenges -- Increased Virulence of Wheat Rusts and the Threat to Global Crop Production -- Fusarium Diseases of Canadian Grain Crops: Impact and Disease Management Strategies -- Pseudomonas fluorescens: A Potential Bio-control Agent for Management of Fungal Diseases of Crop Plants -- Oat Fungal Diseases and the Application of Molecular Marker Technology for Their Control.
Keywords: Life sciences; Microbiology; Plant science; Botany; Plant anatomy; Plant development; Plant pathology; Plant physiology; Plant breeding; Life Sciences; Plant Sciences; Plant Pathology; Microbiology; Plant Anatomy/Development.; Plant Physiology; Plant Breeding/Biotechnology.; Electronic books